efektifitas shake exercise terhadap disfagia pada pasien pasca stroke di rumah sakit cianjur - Intan Lulu; Yeni Koto (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: Stroke is a disease that causes the greatest death and disability every year. Symptoms of stroke that often occur include swallowing disorders or dysphagia. One form of intervention that can be done to speed healing and minimize complications due to dysphagia is to do swallowing exercises. One of the swallowing exercises that can improve swallowing function in stroke patients with dysphagia is the shaker exercise. Purpose: The purpose of this study was to identify the effectiveness of shaker exercise on dysphagia in post-stroke patients and to identify features based on age, gender, education, occupation, on dysphagia in post-stroke patients. Methods: The research design in this study used a quasy experimental design, patients were given intervention for 6 consecutive days of treatment sessions to measure swallowing ability using the GUSS (Gugging Swallowing Screen). Results: After 6 days of treatment sessions, respondents showed a very significant increase in swallowing ability, the average value before treatment was 11.3 and after treatment was 16.5. The effect test results obtained a p-value <0.001 and the result of the effect size was -2.99. Where the intervention of shaker exercise therapy (SE) is effective in increasing the swallowing ability of post-stroke dysphagia patients. Conclusion: The application of shaker exercise (SE) intervention in post-stroke dysphagia patients has significantly improved swallowing ability. It is hoped that those who experience dysphagia can be recommended to carry out shaker exercise independent nursing interventions in treating post-stroke patients with dysphagia.